The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1103/physrevlett.83.5194
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Neutral Atoms Around Curves with Lithographically Patterned Current-Carrying Wires

Abstract: Laser-cooled neutral atoms from a low-velocity atomic source are guided via a magnetic field generated between two parallel wires on a glass substrate. The atoms bend around three curves, each with a 15-cm radius of curvature, while traveling along a 10-cm-long track. A maximum flux of 2 · 10 6 atoms/sec is achieved with a current density of 3 · 10 4 A/cm 2 in the 100 × 100-µm-cross-section wires. The kinetic energy of the guided atoms in one transverse dimension is measured to be 42 µK. PACS numbers: 03.75.B,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
135
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(136 citation statements)
references
References 15 publications
0
135
0
Order By: Relevance
“…By accounting for gravity, atomic fountains can increase the interrogation time during which the interferometry phase shifts accumulate [2]; alternatively one can use magnetic dipole forces to balance the force of gravity [3]. Magnetic waveguides [4,5] can trap atoms for times longer than a second, suggesting the possibility of measuring energy differences between interfering wave packets with an uncertainty <h/(1 s) ∼ 10 −34 J; however, this remarkable precision cannot be obtained if the decoherence time of the atoms is much shorter than the trap lifetime. Early atom interferometry experiments using atoms confined in magnetic waveguides showed that the external state coherence of the atoms decayed quite quickly, limiting interferometric measurements to times <10 ms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…By accounting for gravity, atomic fountains can increase the interrogation time during which the interferometry phase shifts accumulate [2]; alternatively one can use magnetic dipole forces to balance the force of gravity [3]. Magnetic waveguides [4,5] can trap atoms for times longer than a second, suggesting the possibility of measuring energy differences between interfering wave packets with an uncertainty <h/(1 s) ∼ 10 −34 J; however, this remarkable precision cannot be obtained if the decoherence time of the atoms is much shorter than the trap lifetime. Early atom interferometry experiments using atoms confined in magnetic waveguides showed that the external state coherence of the atoms decayed quite quickly, limiting interferometric measurements to times <10 ms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that this "Fermi-Bose duality" is a very general property of identical particles in 1D, not restricted to the hard-sphere model, and relating strongly interacting bosons to weakly-interacting fermions and vice versa. In recent years this esoteric subject has become highly relevant through experiments on ultracold atomic vapors in atom waveguides [3][4][5][6][7][8][9][10][11]. An understanding of their properties is important for atom interferometry [12,13] and integrated atom optics [11,14,15], which are potentially important for development of ultrasensitive detectors of accelerations and gravitational anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first realization of magnetic traps [1,2] and guides [3,4] with current-carrying conductors on a chip, a large variety of magnetic potentials have become experimentally accessible, which would be impractical or even impossible to realize with macroscopic coils. The splitting of two-dimensionally trapped atom clouds has been demonstrated [5,6], and recently, we were able to split and unite a three-dimensionally trapped cloud of rubidium atoms in a chip trap [7].…”
Section: Introductionmentioning
confidence: 99%